Visceral colouration of Eupemphix nattereri (Anura: Leiuperidae): effects of NDP-α-melanocyte stimulating hormone - Franco-Belussi, L. [UNESP]; Freitas, J. Silberschmitd [UNESP]; Oliveira, C. [UNESP] (Taylor & Francis, 2013)
Amphibians have melanin-containing cells in visceral organs that are similar to pigmentary cells from the epidermis. Both of them are derived from the ectodermal neural crest. Epidermal cells respond to α-melanocyte stimulating hormone (α-MSH), which is associated to the dispersion of melanin granules within melanocytes. Therefore, our aim was to test whether a non-degradable analogue of the α-MSH changes the superficial colouration of organs of Eupemphix nattereri. The hormone rapidly increases (within 12 hours) the colouration on the surface of the pericardium, heart, testes, nerves of the lumbar plexus, and lumbosacral parietal peritoneum. Colouration increased late (after 24 hours) in the kidneys and mesentery following hormone administration. However, this hormone did not change colouration of intestine, rectum and lungs. Our findings could be explained by the similarities between epidermal and visceral melanocytes, since both cells have a common embryonic origin. Furthermore, the increase in visceral colouration may be related to the dispersion of melanosomes within melanocytes, which causes the darkening of organs. Our results demonstrate for the first time that the visceral colouration is responsive, thereby altering the internal pattern of organs' colouration in anurans. © 2013 Copyright 2013 Unione Zoologica Italiana.
Keywords: Anura; melanin; melanocytes; melanocytes stimulating hormone; Visceral colouration; amphibian; color morph; hormone; physiological response; Amphibia